A method for recovering iron phosphate from ferrophosphorus slag after lithium extraction, and iron phosphate material and application thereof

By adopting oxidative acid leaching and secondary precipitation processes in the phosphate iron slag after lithium extraction, the problems of high concentration acid use and complex purification in the prior art are solved, and the recovery of high-purity iron phosphate is achieved, which is suitable for battery-level applications.

CN118183651BActive Publication Date: 2025-04-04CENT SOUTH UNIV +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410293796.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-14
Publication Date
2025-04-04
Estimated Expiration
2044-03-14

AI Technical Summary

Technical Problem

In the prior art, when recovering iron phosphate from the phosphate slag after lithium extraction, high concentration of acid is required for leaching, resulting in large amount of acidic solution, complex purification process, and high impurity content of iron phosphate obtained from recovery, making it difficult to meet battery-grade standards.

Method used

The oxidative acid leaching method is used to carry out an oxidative acid leaching reaction of the phosphorus and phosphorus slag after lithium extraction in a lower concentration of acidic solution, and the iron phosphate structure is destroyed by providing potential. Then, a secondary precipitation process is carried out by adjusting the iron-phosphorus ratio and pH value to achieve complete precipitation of iron and phosphorus elements and inhibit impurity precipitation.

Benefits of technology

The complete leaching of iron and phosphorus elements was achieved under the conditions of a lower concentration of acidic solution, which reduced the amount of acidic solution and the precipitation of impurities. The obtained iron phosphate product has high purity and meets battery-grade standards.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118183651B_ABST
    Figure CN118183651B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of lithium iron phosphate recovery, and specifically to a method for recovering iron phosphate from ferrophosphorus slag after lithium extraction, and iron phosphate materials and applications. The method for recovering iron phosphate from ferrophosphorus slag after lithium extraction provided in the present application comprises the following steps: S1, oxidative acid leaching: the ferrophosphorus slag after lithium extraction from waste lithium iron phosphate battery powder is mixed and re-pulped with an acidic solution with a mass concentration of 5% to 20%, and then an oxidant is added thereto for oxidative acid leaching reaction, and after the reaction, filtration is performed to obtain ferrophosphorus liquid; S2, precipitation: after adjusting the iron-phosphorus ratio of the ferrophosphorus liquid, the pH is adjusted so that the iron phosphate is precipitated from the system, and solid-liquid separation is performed; S3, post-treatment: the solid phase material obtained by solid-liquid separation in S2 is washed, dried and calcined to obtain iron phosphate. The method has the advantages of simple process, high recovery rate of iron and phosphorus components, and high product purity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium iron phosphate recovery, and in particular to a method for recovering iron phosphate from ferrophosphorus slag after lithium extraction, and an iron phosphate material and application. Background Art

[0002] With the rapid growth of the global electric vehicle market, the market demand for batteries, as one of the core components of electric vehicles, will continue to grow. With its price and cost advantages, easier access to raw materials, long cycle life, low self-discharge rate, no memory effect, and no environmental pollution, more automakers have chosen lithium iron phosphate batteries. Lithium iron phosphate batteries use lithium iron phosphate (LiFePO4) as the positive electrode material. Due to the characteristics of the battery itself, its life is generally 5 to 8 years. With the continued growth of electric vehicles, it is expected that a large number of power batteries will be retired in the future, and it is urgent to solve the problem of power battery resource recycling and reuse.

[0003] After lithium recovery from lithium iron phosphate batteries, a large amount of crude ferrophosphorus slag will be generated. The crude ferrophosphorus slag is mainly composed of iron phosphate, carbon slag and a small amount of impurities, of which the iron content is 28% to 32%, the phosphorus content is 17% to 19%, and the carbon content is 0.5% to 3%. In order to achieve a higher leaching rate, the prior art generally uses high-concentration acid to leach the phosphorus and iron elements in the crude ferrophosphate slag after lithium extraction, and then dilutes it with water and adjusts the pH to prepare dihydrated iron phosphate, and uses alkali to neutralize the acid. Due to the high concentration of the added acid, a large amount of alkali needs to be added for neutralization, resulting in a large amount of high-salt wastewater. In order to reduce the content of other metal elements in the recovered iron phosphate, some prior arts use iron replacement copper removal and resin aluminum removal methods to purify the leachate, resulting in a complicated recovery process, and new impurity ions may be introduced during the impurity removal process. The prepared iron phosphate has a high impurity content and is difficult to meet the requirements of battery-grade iron phosphate. Summary of the invention

[0004] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a method for recovering iron phosphate from ferrophosphorus slag after lithium extraction, an iron phosphate material and an application, which can solve at least one of the problems of recovering iron phosphate from ferrophosphorus slag after lithium extraction in the prior art, namely, the need to use high-concentration acid for acid leaching, the complex purification process and the high impurity content of the recovered iron phosphate.

[0005] In order to achieve the above object, the present invention adopts the following technical solution:

[0006] The first aspect of the present invention is to provide a method for recovering ferric phosphate from ferrophosphorus slag after lithium extraction, comprising the following steps:

[0007] S1, oxidative acid leaching: the ferrophosphorus slag after lithium extraction from waste lithium iron phosphate battery powder is mixed with an acid solution with a mass concentration of 5% to 20% and then re-pulped, and then an oxidant is added thereto for oxidative acid leaching reaction, and after the reaction, the ferrophosphorus liquid is obtained by filtering;

[0008] S2, precipitation: after adjusting the iron-phosphorus ratio of the ferrophosphorus solution, adjusting the pH so that the ferrophosphate is precipitated from the system, and performing solid-liquid separation;

[0009] S3, post-processing: washing, drying and calcining the solid phase material obtained by solid-liquid separation in S2 to obtain iron phosphate.

[0010] Furthermore, the oxidant in S1 is selected from at least one of hydrogen peroxide and ammonium persulfate;

[0011] And / or, the mass concentration of the oxidant solution in S1 is 5% to 8%;

[0012] And / or, the oxidant solution in S1 is added in an amount of 30 g / L to 60 g / L of acidic solution.

[0013] Furthermore, the acidic solution in S1 is selected from at least one of nitric acid, sulfuric acid and hydrochloric acid;

[0014] And / or, the mass concentration of the acidic solution in S1 is 5% to 8%;

[0015] And / or, in S1, the phosphorus iron slag obtained after lithium extraction from waste lithium iron phosphate battery powder is mixed with an acid solution and re-pulped at a solid-liquid ratio of 100 g / L to 300 g / L.

[0016] Furthermore, the leaching temperature used in the oxidative acid leaching in S1 is 50° C. to 90° C., and the leaching time is 1 h to 4 h.

[0017] Furthermore, the precipitation in S2 adopts a secondary precipitation process, comprising the following steps:

[0018] S21, primary precipitation: adjusting the iron-phosphorus ratio of the ferrophosphorus liquid to 1.02-1.08:1, adjusting the pH to 1.3-2.2 with alkali, performing the first precipitation reaction at 45°C-65°C, the reaction time is 30min-90min, and after the insulation is completed, performing solid-liquid separation on the slurry;

[0019] S22, secondary precipitation: the solid phase material obtained by the solid-liquid separation of S2 is mixed with water for re-slurry, the pH is adjusted to 1.2-2.2, and a second precipitation reaction is carried out at 85°C-105°C for 2h-4h. After the insulation is completed, the slurry is subjected to solid-liquid separation.

[0020] Furthermore, the method for adjusting the phosphorus-iron ratio of the ferrophosphorus liquid is: adding ferrous sulfate, phosphate and oxidant to the ferrophosphorus liquid in sequence until the iron-phosphorus ratio in the system is 1.02-1.08:1 and the Fe concentration in the system is 1.5 mol / L-3 mol / L;

[0021] Preferably, the phosphate is at least one of monoammonium phosphate and phosphoric acid;

[0022] Preferably, the oxidant used is hydrogen peroxide, and the amount of hydrogen peroxide used is 1 to 1.5 times the molar amount of iron in the system.

[0023] Furthermore, the base in S21 is selected from at least one of aqueous ammonia and sodium hydroxide.

[0024] and / or, S21 adjusting the pH to 1.3-1.8 using alkali;

[0025] And / or, S22 adjusts the pH to 1.2-1.6.

[0026] Furthermore, the solid content of the solid phase material mixed with water in S22 for re-slurrying is 10% to 15%;

[0027] And / or, the reagent used to adjust the pH to 1.2-2.2 in S22 is selected from at least one of phosphoric acid and sulfuric acid.

[0028] The second aspect of the present invention is to provide an iron phosphate material, which is prepared by the above method.

[0029] The third aspect of the present invention is to provide the use of the iron phosphate as a raw material for preparing lithium iron phosphate batteries;

[0030] Preferably, the iron phosphate is battery grade iron phosphate.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] 1. The method for recovering iron phosphate from ferrophosphorus slag after lithium extraction provided in the present application, the oxidant added during the oxidative acid leaching process can provide a potential to destroy the stable iron phosphate structure in the ferrophosphorus slag under the condition of a relatively low concentration of acidic solution, and achieves complete leaching of iron and phosphorus elements at a concentration of 5% to 8% of the acidic solution, effectively reducing the concentration and dosage of the acidic solution.

[0033] 2. In the above technical scheme of the present application, after the phosphorus-iron ratio of the ferrophosphorus liquid obtained by oxidative acid leaching is adjusted, a secondary precipitation process is adopted. By controlling the pH, reaction time and temperature of the two precipitations, a slurry mainly composed of basic ferric phosphate is obtained by the first precipitation, and then the solid phase material in the slurry is re-slurried and a second precipitation is performed to obtain a slurry mainly composed of dihydrate ferric phosphate. Through process and condition control, almost complete precipitation of iron and phosphorus elements is achieved, while the precipitation of impurity elements is suppressed, and the resulting ferrophosphate product has high purity. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 The process flow chart of the method for recovering ferric phosphate from ferrophosphorus slag after lithium extraction of the present invention;

[0035] Figure 2 is the XRD diagram of anhydrous ferric phosphate in Example 4 of the present invention;

[0036] Figure 3 This is a SEM image of anhydrous ferric phosphate in Example 4 of the present invention. DETAILED DESCRIPTION

[0037] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. The described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] The present invention provides a method for recovering iron phosphate from ferrophosphorus slag after lithium extraction. The method is suitable for recovering ferrophosphorus slag after lithium extraction from lithium iron phosphate batteries. Specifically, the method comprises the following steps:

[0039] S1, oxidative acid leaching: the ferrophosphorus slag after lithium extraction from waste lithium iron phosphate battery powder is mixed with an acid solution with a mass concentration of 5% to 8% and then re-pulped, and then an oxidant is added thereto for oxidative acid leaching reaction, and after the reaction, the ferrophosphorus liquid is obtained by filtering;

[0040] S2, precipitation: after adjusting the iron-phosphorus ratio of the ferrophosphorus solution, adjusting the pH so that the ferrophosphate is precipitated from the system, and performing solid-liquid separation;

[0041] S3, post-processing: washing, drying and calcining the solid phase material obtained by solid-liquid separation in S2 to obtain iron phosphate.

[0042] It should be noted that the waste lithium iron phosphate battery powder used in the above method includes but is not limited to scrapped lithium iron phosphate batteries, unqualified lithium iron phosphate batteries, unqualified lithium iron phosphate raw materials, etc. The "re-slurry" involved in this application refers to the process of dispersing solid materials in liquid materials to form slurry.

[0043] The above-mentioned method for recovering iron phosphate from ferrophosphorus slag after lithium extraction provided by the present application, in the process of oxidative acid leaching, firstly adds an acidic solution for mixing and then slurrying to dissolve most of the crude iron phosphate, and then adds an oxidant, which can provide an oxidation potential, so that the stable iron phosphate structure in the ferrophosphorus slag is destroyed under the condition of a relatively low concentration of acidic solution, and the amount of acid can be reduced, thereby promoting the dissolution of the remaining iron phosphate. Complete leaching of iron and phosphorus elements is achieved under the condition of a relatively low concentration of acidic solution, effectively reducing the concentration and amount of acidic solution.

[0044] The composition of ferrophosphorus slag is mainly ferrophosphate, carbon slag and a small amount of impurities, among which the iron content is 28% to 32%, the phosphorus content is 17% to 19%, and the carbon content is 0.5% to 3%.

[0045] In some preferred embodiments, the oxidant in S1 is selected from at least one of hydrogen peroxide and ammonium persulfate; and / or, the mass concentration of the oxidant solution in S1 is 5% to 8%; and / or, the amount of the oxidant solution in S1 is added according to 30g / L to 60g / L of acidic solution. As an example, the amount of the oxidant solution used is 30g / L, 35g / L, 40g / L, 45g / L, 50g / L, 55g / L, 60g / L or any value in the range; for example, 30g / L should be understood as the weight of the oxidant solution added to 1L of acidic solution is 30g.

[0046] In other preferred embodiments, the acidic solution in S1 is selected from at least one of nitric acid, sulfuric acid and hydrochloric acid; and / or, the mass concentration of the acidic solution in S1 is 5% to 8%; and / or, the solid-liquid ratio adopted in S1 for mixing the ferrophosphorus slag with the acidic solution after lithium extraction from the waste lithium iron phosphate battery powder and re-slurrying is 100g / L to 300g / L. As an example, the solid-liquid ratio adopted can be, for example, 100g / L, 200g / L, 300g / L, or any value within the range; for example, 100g / L should be understood as the weight of ferrophosphorus slag added to 1L of acidic solution is 100g.

[0047] In other preferred embodiments, the leaching temperature used in the oxidative acid leaching in S1 is 50°C to 90°C, and the leaching time is 1h to 4h. As an example, the leaching temperature used can be, for example, 50°C, 60°C, 70°C, 80°C, 90°C, or a range consisting of any two of the above values. The leaching temperature used can be, for example, 1h, 2h, 3h, 4h, or any value within the range.

[0048] In some other preferred embodiments, the precipitation in S2 adopts a secondary precipitation process, comprising the following steps:

[0049] S21, primary precipitation: adjusting the iron-phosphorus ratio of the ferrophosphorus liquid to 1.02-1.08:1, adjusting the pH to 1.3-2.2 with alkali, performing the first precipitation reaction at 45-65° C., the reaction time is 30 min-90 min, and after the insulation is completed, performing solid-liquid separation on the slurry;

[0050] S22, secondary precipitation: the solid phase material obtained by the solid-liquid separation of S2 is mixed with water for re-slurry, the pH is adjusted to 1.2-2.2, and a second precipitation reaction is carried out at 85°C-105°C for 2h-4h. After the insulation is completed, the slurry is subjected to solid-liquid separation.

[0051] In the above technical scheme of the present application, after the phosphorus-iron ratio of the ferrophosphorus liquid obtained by oxidative acid leaching is adjusted, a secondary precipitation process is adopted. By controlling the pH, reaction time and temperature of the two precipitations, a slurry mainly composed of basic ferric phosphate is obtained by the first precipitation, and then the solid phase material in the slurry is re-slurried and a second precipitation and crystallization are performed to obtain a slurry mainly composed of dihydrate ferric phosphate. Through process and condition control, almost complete precipitation of iron and phosphorus elements is achieved, while the precipitation of impurity elements is suppressed, and the resulting ferrophosphate product has high purity.

[0052] Compared with the methods of the prior art, the present application does not need to adopt a complicated purification method, and no other reagents need to be added during the precipitation process except for pH adjustment, so that high-purity iron phosphate can be obtained.

[0053] In some preferred embodiments, the method for adjusting the phosphorus-iron ratio of the ferrophosphorus liquid is: adding ferrous sulfate, phosphate and oxidant to the ferrophosphorus liquid in sequence until the iron-phosphorus ratio in the system is 1.02-1.08:1, and the Fe concentration in the system is 1.5 mol / L-3 mol / L; as an example, the iron-phosphorus ratio can be, for example, 1.02, 1.03, 1.04, 1.05, 1.06, 1.07, 1.08 or any value within the above range; the Fe concentration in the system can be, for example, 1.5 mol / L, 2 mol / L, 2.5 mol / L, 3 mol / L or any value within the above range.

[0054] Preferably, in adjusting the phosphorus-iron ratio, the phosphate used is at least one of monoammonium phosphate and phosphoric acid;

[0055] Preferably, in adjusting the phosphorus-iron ratio, the oxidant used is hydrogen peroxide, and the amount of hydrogen peroxide used is 1 to 1.5 times the molar amount of iron in the system, so that Fe 2+ Can be completely oxidized to Fe 3+ .

[0056] The above-mentioned method for adjusting the phosphorus-iron ratio is to add the raw materials for synthesizing iron phosphate without introducing additional impurities. This step can also increase the pH value of the system and reduce the amount of alkali added for a single precipitation.

[0057] In some other preferred embodiments, the base in S21 is selected from at least one of aqueous ammonia and sodium hydroxide;

[0058] and / or, S21 adjusting the pH to 1.3-1.8 using alkali;

[0059] And / or, S22 adjusts the pH to 1.2-1.6.

[0060] In a preferred embodiment, the solid content of the solid phase material mixed with water for re-slurrying in S22 is 10% to 15%.

[0061] In a preferred embodiment, the reagent used to adjust the pH to 1.2-2.2 in S22 is selected from at least one of phosphoric acid and sulfuric acid.

[0062] The present invention also provides an iron phosphate material, which is prepared by the above method.

[0063] The present invention also provides the use of the above-mentioned iron phosphate as a raw material for preparing lithium iron phosphate batteries; preferably, the iron phosphate is battery-grade iron phosphate.

[0064] The methods are conventional methods unless otherwise specified, and the raw materials can be obtained from public commercial channels unless otherwise specified.

[0065] The following is a further explanation of the method for recovering iron phosphate from ferrophosphorus slag after lithium extraction in the present application in conjunction with the drawings in the specification.

[0066] Example 1: Leaching Fe and P from ferrophosphorus slag

[0067] The crude ferrophosphorus slag was mixed with 6% sulfuric acid solution to form a slurry, and a 6% hydrogen peroxide solution was added in an amount of 40g / L. The solid-liquid ratio of the system was 200g / L, the leaching temperature was 90°C, and the leaching time was 1h. After the leaching reaction was completed, the slurry was separated from the solid and liquid to obtain leached slag and ferrophosphorus liquid.

[0068] The leaching rates of the oxidation leaching reaction are: 99.88% for Fe element and 99.80% for P element.

[0069] Example 2: Leaching Fe and P from ferrophosphorus slag

[0070] The crude ferrophosphorus slag was mixed with 6% sulfuric acid solution to form a slurry, and a 6% ammonium persulfate solution was added in an amount of 40 g / L. The solid-liquid ratio of the system was 200 g / L, the leaching temperature was 90°C, and the leaching time was 1 h. After the leaching reaction was completed, the slurry was separated into solid and liquid to obtain leached slag and ferrophosphorus liquid.

[0071] The leaching rates of the oxidation leaching reaction are: 99.87% for Fe element and 99.76% for P element.

[0072] Example 3: Leaching Fe and P from ferrophosphorus slag

[0073] The method of Example 1 was followed, except that the concentration of sulfuric acid used was 5%. The leaching rates were: 95.30% for Fe element and 94.76% for P element.

[0074] Comparative Example 1: Leaching Fe and P from ferrophosphorus slag

[0075] The method of Example 1 is different in that no hydrogen peroxide is added, and only the crude ferrophosphorus slag is mixed with 6% sulfuric acid solution to form a slurry. The leaching rates are: 45.08% for Fe element and 44.57% for P element.

[0076] Comparative Example 2: Leaching Fe and P from ferrophosphorus slag

[0077] The method of Example 1 is different in that the concentration of sulfuric acid used is 4.75%. The leaching rates are: 81.05% for Fe element and 80.63% for P element.

[0078] It can be seen that compared with Example 1, no oxidant was added during the oxidative acid leaching process in Comparative Example 1, and the leaching rates of Fe and P elements were significantly lower than those in Example 1, reduced by about 55%. In addition, it should be noted that during the leaching process, the concentration of sulfuric acid used should not be lower than 5%, otherwise the leaching rates of Fe and P elements will be greatly reduced.

[0079] Example 4: Preparation of anhydrous ferric phosphate from ferrophosphorus liquid

[0080] Take monoammonium phosphate solution and ferrous sulfate solution and add them to the above-obtained ferrophosphorus liquid (Example 1), control the Fe molar concentration in the reaction system to be 2.0 mol / L, the system iron-phosphorus ratio to be 1.05, and then drop 1.4 times the molar amount of iron in hydrogen peroxide until all the divalent iron in the system is oxidized to trivalent iron. After the oxidation is complete, heat to 50°C, add ammonia water to adjust the system pH to 1.50, keep warm for 60 minutes, separate the slurry solid and liquid after the insulation is completed, wash the filter cake and mix it with water to re-slurry, control the solid content to 10%, use sulfuric acid: phosphoric acid: water = 3:3:14 mixed acid to adjust the slurry pH to 1.50, heat to 90°C and keep warm for 2 hours to obtain iron phosphate slurry. The precipitation rate is: Fe element 97.75%, P element 97.54%.

[0081] The obtained ferric phosphate slurry is separated into solid and liquid, and washed to obtain a solid phase material of ferric phosphate dihydrate. The solid phase material is dried and calcined to obtain anhydrous ferric phosphate product.

[0082] After analysis, the obtained anhydrous ferric phosphate product has Fe / P=0.9667, Al content is 0.0034%, Ca content is 0.0005%, Mg content is 0.0008%, Cu content is ND, Ni content is ND, Co content is 0.0002%, and Zn content is 0.0001%.

[0083] Figure 2 is the XRD characterization diagram of the anhydrous ferric phosphate, Figure 3 : is a SEM scanning electron microscope image of the anhydrous ferric phosphate. The result shows that the anhydrous ferric phosphate prepared in this embodiment has a flaky structure, which is stacked with some pores, and the overall particle size is small.

[0084] Example 5: Preparation of anhydrous ferric phosphate from ferrophosphorus liquid

[0085] Take monoammonium phosphate solution and ferrous sulfate solution and add them to the above-obtained ferrophosphorus liquid (Example 2), control the Fe molar concentration in the reaction system to be 2.0 mol / L, the system iron-phosphorus ratio to be 1.05, and then drop 1.4 times the molar amount of iron in hydrogen peroxide until all the divalent iron in the system is oxidized to trivalent iron. After the oxidation is complete, heat to 50°C, add ammonia water to adjust the system pH to 1.70, keep warm for 60 minutes, separate the slurry solid and liquid after the insulation is completed, wash the filter cake and mix it with water to re-slurry, control the solid content to 10%, use sulfuric acid: phosphoric acid: water = 3:3:14 mixed acid to adjust the slurry pH to 1.50, heat to 90°C and keep warm for 2 hours to obtain iron phosphate slurry. The precipitation rate is: Fe element 97.40%, P element 97.32%.

[0086] The obtained ferric phosphate slurry is separated into solid and liquid, and washed to obtain a solid phase material of ferric phosphate dihydrate. The solid phase material is dried and calcined to obtain anhydrous ferric phosphate product.

[0087] In the anhydrous ferric phosphate product, Fe / P=0.9660, Al content is 0.0045%, Ca content is 0.0007%, Mg content is 0.0009%, Cu content is ND, Ni content is ND, Co content is 0.0004%, and Zn content is 0.0002%.

[0088] Comparative Example 3

[0089] The crude ferrophosphorus slag is mixed with 6% sulfuric acid solution to form a slurry, and a 6% hydrogen peroxide solution is added in an amount of 40g / L. The solid-liquid ratio of the system is 200g / L, the leaching temperature is 90°C, and the leaching time is 1h. After the leaching reaction is completed, the slurry is separated into solid and liquid to obtain leached slag and ferrophosphorus liquid; the leaching rates of the oxidation leaching reaction are: 99.85% for Fe element and 99.79% for P element.

[0090] Take monoammonium phosphate solution and ferrous sulfate solution and add them to the above-mentioned phosphorus iron liquid, control the Fe molar amount in the reaction system to 2.0 mol, the system iron-phosphorus ratio to 1.05, heat to 50°C, add ammonia water to adjust the system pH to 1.50, keep warm for 60 minutes, separate the slurry solid and liquid after the insulation is completed, wash the filter cake and mix it with water to re-slurry, control the solid content to 10%, use sulfur-phosphorus mixed acid to adjust the slurry pH to 1.50, heat to 90°C and keep warm for 2 hours to obtain slurry; precipitation rate: Fe element 89.75%, P element 89.63%. Since the precipitation pH control value in the first stage precipitation process is 1.50, hydrogen peroxide plays the role of oxidation to precipitate iron and phosphorus elements here, and since no hydrogen peroxide is added, the yield of iron and phosphorus elements is reduced.

[0091] The obtained ferric phosphate slurry is separated into solid and liquid, and washed to obtain a solid phase material of ferric phosphate dihydrate. The solid phase material is dried and calcined to obtain anhydrous ferric phosphate product.

[0092] In the anhydrous ferric phosphate product, Fe / P=0.9659, Al content is 0.0041%, Ca content is 0.0009%, Mg content is 0.0013%, Cu content is ND, Ni content is ND, Co content is 0.0005%, and Zn content is 0.0004%.

[0093] It should be noted that the test methods used in the leaching and purification processes in the above embodiments and comparative examples are as follows:

[0094] (1) Iron molar mass test: The mass of iron in the lithium extraction slag or leaching solution is tested using an inductively coupled plasma emission spectrometer. The iron molar mass is the mass obtained by the test divided by the relative atomic mass of iron.

[0095] (2) Leaching rate test: The leaching rate of iron and phosphorus in the crude ferrophosphorus slag after lithium extraction from waste lithium iron phosphate battery powder refers to the percentage ratio of the difference between the content of iron and phosphorus in the crude ferrophosphorus slag and the content of iron and phosphorus in the leached slag to the content of iron and phosphorus in the lithium extraction slag.

[0096] (3) Precipitation rate test: The precipitation rate of iron and phosphorus in the iron phosphate precipitation process refers to the percentage ratio of the difference between the content of iron and phosphorus in the liquid before precipitation and the content of iron and phosphorus in the liquid after precipitation to the content of iron and phosphorus in the liquid before precipitation.

[0097] (4) Impurity content test: The mass of impurities in the anhydrous ferric phosphate product is tested by inductively coupled plasma emission spectrometry. The impurity content is the mass of the impurities obtained by the test divided by the total mass of the anhydrous ferric phosphate product.

[0098] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present application and not to limit it. Although the present application has been described in detail with reference to the preferred embodiments, ordinary technicians in the relevant field should understand that the specific implementation methods of the present application can still be modified or some technical features can be replaced by equivalents, which should all be included in the scope of the technical solution requested for protection in this application.

Claims

1. A method for recovering ferric phosphate from ferrophosphorus slag after lithium extraction, characterized in that: The following steps are involved: S1. Oxidative acid leaching: the ferrophosphorus slag obtained after lithium extraction from waste lithium iron phosphate battery powder is mixed with an acid solution having a mass concentration of 5% to 8% and then re-pulped, and then an oxidant is added thereto for oxidative acid leaching reaction, and after the reaction, the ferrophosphorus liquid is obtained by filtering; S2, precipitation: after adjusting the iron-phosphorus ratio of the ferrophosphorus liquid, adjusting the pH so that the ferrophosphate is precipitated from the system, and performing solid-liquid separation; the precipitation described in S2 adopts a secondary precipitation process, comprising the following steps: S21, primary precipitation: adjusting the iron-phosphorus ratio of the ferrophosphorus liquid to 1.02-1.08:1, the Fe concentration in the system is 1.5 mol / L-3 mol / L; adjusting the pH to 1.3-1.8 with alkali, performing the first precipitation reaction at 45°C-65°C, the reaction time is 30min-90min, and after the insulation is completed, performing solid-liquid separation on the slurry; S22, secondary precipitation: the solid phase material obtained by solid-liquid separation of S2 is mixed with water for re-slurry, the pH is adjusted to 1.2-1.6, and a second precipitation reaction is carried out at 85°C-105°C for 2h-4h. After the insulation is completed, the slurry is subjected to solid-liquid separation; S3, post-processing: washing, drying and calcining the solid phase material obtained by solid-liquid separation in S2 to obtain iron phosphate; S1: The oxidant is selected from at least one of hydrogen peroxide and ammonium persulfate; The mass concentration of the oxidant solution in S1 is 5% to 8%; The amount of the oxidant solution in S1 is added according to 30 g / L to 60 g / L of acidic solution.

2. The method according to claim 1, characterized in that: S1: the acidic solution is selected from at least one of nitric acid, sulfuric acid and hydrochloric acid; And / or, in S1, the ferrophosphorus slag obtained after lithium extraction from waste lithium iron phosphate battery powder is mixed with an acidic solution and re-pulped at a solid-liquid ratio of 100 g / L to 300 g / L.

3. The method according to any one of claims 1 to 2, characterized in that: The leaching temperature of the oxidative acid leaching in S1 is 50°C to 90°C, and the leaching time is 1h to 4h.

4. The method according to claim 1, characterized in that The method for adjusting the phosphorus-iron ratio of the ferrophosphorus liquid is as follows: ferrous sulfate, phosphate and oxidant are sequentially added to the ferrophosphorus liquid until the iron-phosphorus ratio in the system is 1.02-1.08:1, The oxidant used is hydrogen peroxide, and the amount of hydrogen peroxide used is 1 to 1.5 times the molar amount of iron in the system.

5. The method according to claim 4, characterized in that The phosphate used is at least one of monoammonium phosphate and phosphoric acid.

6. The method according to claim 4, characterized in that In S22, the solid content used for mixing the solid phase material with water and re-slurrying is 10% to 15%; And / or, the reagent used to adjust the pH to 1.2-2.2 in S22 is selected from at least one of phosphoric acid and sulfuric acid.

Citation Information

Patent Citations

  • Synthesis process of battery-grade iron phosphate

    CN110540185A

  • Method for recycling multi-impurity waste lithium iron phosphate black powder

    CN115583640A